Kesulitan Siswa Dalam Menangkap Pembelajaran Di Kelas - Amelia Rika Fadillah; Fadilah Fadilah; Tia Anggraini Silalahi; Winda Amelia Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine students' difficulties in capturing learning and the factors that make students have difficulty learning. This research uses library research which is intended to describe students' difficulties in capturing learning. The results of the research are that there are factors that cause students to have difficulty learning, including; Internal factors and external factors. These internal factors come from the student, such as the student's IQ, student's attitude towards learning, motivation to learn, body health, and sensory abilities. Meanwhile, these external factors are caused by factors outside the student, including teacher variations in teaching, use of learning media, school infrastructure, and family environment.